Accurate determination of viscosity and surface tension by surface light scattering in the presence of a contribution from the rotational flow in the bulk of the fluid - Koller, Thomas Manfred; Kerscher, Manuel; Fröba, Andreas Paul (Journal of Colloid and Interface Science, 2022)
Hypothesis: Near the critical damping of surface fluctuations, surface light scattering (SLS) signals are affected by the rotational flow in the bulk of the fluid. The adequate consideration of this bulk shear mode is essential for a reliable determination of viscosity and surface tension, yet not fully resolved so far. Experiments: To elucidate the influence of the bulk shear mode on the recorded correlation functions related to surface fluctuations with an oscillatory behavior, different evaluation procedures are compared. A new evaluation approach is suggested, which makes use of the entire signal information and represents the contribution of the bulk shear mode to the signal in a convenient and physically meaningful way. This allows to unambiguously access the dynamics of the probed surface fluctuations, i.e. their mean lifetime and frequency as well as their response to the rotational flow in the bulk of the fluid. Findings: By applying the evaluation approach to SLS signals for eight different vapor–liquid systems corresponding to reduced capillary numbers between about 0.4 and 15, it is demonstrated that the developed strategy allows for an accurate determination of viscosity and surface tension. This strategy facilitates the thermophysical property research on fluids by SLS experiments performed close to the critical damping.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Bulk shear mode; Capillary waves; Correlation function; Critical damping; Rotational flow; Surface light scattering; Surface tension; Viscosity

Characterization of Long Linear and Branched Alkanes and Alcohols for Temperatures up to 573.15 K by Surface Light Scattering and Molecular Dynamics Simulations - Klein, Tobias; Lenahan, Frances; Kerscher, Manuel; Rausch, Michael Heinrich; Economou, Ioannis G.; Koller, Thomas Manfred; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2020)
This work contributes to the characterization of long linear and branched alkanes and alcohols via the determination of their thermophysical properties up to temperatures of 573.15 K. For this, experimental techniques including surface light scattering (SLS) and molecular dynamics (MD) simulations were used under equilibrium conditions to analyze the influences of chain length, branching, and hydroxylation on liquid density, liquid viscosity, and surface tension. For probing these effects, 12 pure model systems given by the linear alkanes n-dodecane, n-hexadecane, n-octacosane, n-triacontane, and n-tetracontane, the linear alcohols 1-dodecanol, 1-hexadecanol, and 1,12-dodecanediol, the branched alkanes 2,2,4,4,6,8,8-heptamethylnonane (HMN) and 2,6,10,15,19,23-hexamethyltetracosane (squalane), and the branched alcohols 2-butyl-1-octanol and 2-hexyl-1-decanol were investigated at or close to saturation conditions at temperatures between 298.15 and 573.15 K. Based on the experimental results for the liquid densities, liquid viscosities, and surface tensions with average expanded uncertainties (k = 2) of 0.061, 2.1, and 2.6%, respectively, the performance of the three commonly employed force fields (FFs) TraPPE, MARTINI, and L-OPLS was assessed in MD simulations. To improve the simulation results for the best-performing all-atom L-OPLS FF at larger temperatures, a modified version was suggested. This incorporates a temperature dependence for the energy parameters of the Lennard-Jones potential obtained by calibrating only against the experimental liquid density data of n-dodecane. By transferring this approach to all other systems studied, the modified L-OPLS FF shows now a distinctly better representation of the equilibrium and transport properties of the long alkanes and alcohols, especially at high temperatures.
CRIS-Team Scopus Importer:2020-06-02

Determination of hydrogen loading in the carrier system diphenylmethane/dicyclohexylmethane by depolarized Raman spectroscopy - Jander, Julius Hans; Kerscher, Manuel; Li, Shao; Rausch, Michael Heinrich; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
During the processes of hydrogenation or dehydrogenation of liquid organic hydrogen carriers (LOHCs), knowledge of the current degree of hydrogenation (DoH) is often essential. The present study shows that depolarized Raman spectroscopy allows the accurate determination of the DoH of the model LOHC system diphenylmethane (H0-DPM)/dicyclohexylmethane (H12-DPM) at temperatures up to 573 K. Using two independent experimental setups and binary mixtures of H0- and H12-DPM, a temperature-independent calibration factor could be obtained by analyzing Raman bands characteristic for the aromatic and aliphatic carbon rings. The successful transfer of the calibration to technical mixtures is validated by DoH measurements of samples from deliberately stopped hydrogenation reactions containing also the intermediate cyclohexylphenylmethane (H6-DPM) and of pure H6-DPM. Here, the average absolute deviation of the DoHs obtained by depolarized Raman spectroscopy from those measured analytically is 0.018, which demonstrates the applicability of the method at arbitrary and process-relevant temperatures.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Degree of hydrogenation; Depolarized Raman spectroscopy; Diphenylmethane; In-situ process monitoring; LOHC

Diffusivities in 1-alcohols containing dissolved H2, He, N2, CO, or CO2 close to infinite dilution - Wu, Wenchang; Klein, Tobias; Kerscher, Manuel; Rausch, Michael Heinrich; Koller, Thomas Manfred; Giraudet, Cédric; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2019)
The influence of the strength of intermolecular interactions on mass diffusive processes remains poorly understood for mixtures of associative liquids with dissolved gases. For contributing to a fundamental understanding on the interplay between liquid structure and mass diffusivities in such systems, dynamic light scattering, Raman spectroscopy, and molecular dynamics simulations were used in this work. As model systems, binary mixtures consisting of the gases hydrogen, helium, nitrogen, carbon monoxide, or carbon dioxide dissolved in ethanol, 1-hexanol, or 1-decanol were selected. Experiments and simulations were performed at macroscopic thermodynamic equilibrium close to infinite dilution of solute for temperatures between (303 and 423) K. The Fick diffusion coefficients and self-diffusivities of the gas solutes increase with increasing temperature, decreasing alkyl chain length of the 1-alcohols, and decreasing molar mass of the solutes except for helium and hydrogen showing the opposite behavior. The analysis of the liquid structure of the mixtures showed that the fraction of hydrogen-bonded alcohol molecules was found to decrease with increasing alkyl chain length and temperature. From the obtained structure-property relationships, a new correlation was developed to predict mass diffusivities in binary mixtures consisting of n-alkanes or 1-alcohols with dissolved gases close to infinite dilution within 10% on average.
CRIS-Team Scopus Importer:2019-10-15

Effect of the degree of hydrogenation on the viscosity, surface tension, and density of the liquid organic hydrogen carrier system based on diphenylmethane - Schmidt, Patrick; Kerscher, Manuel; Klein, Tobias; Jander, Julius Hans; Bioucas, Francisco; Rüde, Timo; Li, Shao; Stadelmaier, Monika; Hanyon, Samantha; Fathalla, Ramy; Bösmann, Andreas; Preuster, Patrick; et al. (International Journal of Hydrogen Energy, 2022)
For the efficient design of hydrogenation and dehydrogenation processes, a comprehensive database for the viscosity, surface tension, and density of mixtures of the diphenylmethane-based liquid organic hydrogen carrier system and the pure intermediate cyclohexylphenylmethane measured by complementary optical and conventional methods and calculated by molecular dynamics simulations at process-relevant temperatures up to 623 K is presented. The simulations employ self-developed force fields including a new one for cyclohexylphenylmethane and reveal surface enrichment and orientation effects influencing the surface tension. Relatively simple correlation and prediction approaches yield accurate representations as function of temperature and degree of hydrogenation (DoH) of the mixtures with average absolute relative deviations (AARD) of 0.07% for the density and 2.9% for the surface tension. Application of the extended hard sphere theory considering the presented accurate density data allows capturing the highly nonlinear DoH-dependent behavior of the dynamic viscosity with an AARD of 2.9%. (c) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Density; Experiment; LOHC mixtures; Modeling; Surface tension; Viscosity

Influence of dissolved hydrogen on the viscosity and interfacial tension of the liquid organic hydrogen carrier system based on diphenylmethane by surface light scattering and molecular dynamics simulations - Kerscher, Manuel; Klein, Tobias; Preuster, Patrick; Wasserscheid, Peter; Koller, Thomas Manfred; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
In hydrogenation and dehydrogenation processes of liquid organic hydrogen carriers (LOHCs), molecular hydrogen (H2) is present, but its influence on the thermophysical properties of the LOHC compounds is still hardly known. This study provides experimental results from surface light scattering and predictions from molecular dynamics simulations on the influence of dissolved H2 on the liquid viscosity, interfacial tension, and liquid density of the LOHC system based on diphenylmethane at varying degree of hydrogenation, process-relevant temperatures up to 573 K, and pressures up to 7 MPa. First-time measurements of the viscosity of bicyclic hydrocarbon compounds in the presence of dissolved H2 at saturation conditions reveal a negligible effect of pressure. The interfacial tension decreases independently of the LOHC composition by about 6% at 7 MPa. The simulations can adequately represent the effect of H2 on the interfacial tension and evidence a weak enrichment of H2 at the interface.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Density; Dissolved hydrogen; Interfacial tension; LOHC systems; Pressure; Viscosity

Mutual and Thermal Diffusivities as Well as Fluid-Phase Equilibria of Mixtures of 1-Hexanol and Carbon Dioxide - Wu, Wenchang; Klein, Tobias; Kerscher, Manuel; Rausch, Michael Heinrich; Koller, Thomas Manfred; Giraudet, Cédric; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2020)
This work contributes to an improved understanding of the fluid-phase behavior and diffusion processes in mixtures of 1-hexanol and carbon dioxide (CO2) at temperaturesaround the upper critical end point (UCEP) of the system. Raman spectroscopy and dynamic light scattering were used to determine the composition at saturation conditions as well as Fick and thermal diffusivities. An acceleration of the Fick diffusive process up to CO2 mole fractions of about 0.2 was found, followed by a strong slowing-down approaching vapor−liquid−liquid equilibrium or critical conditions. The acceleration of the Fick diffusive process vanished at temperatures much higher than the UCEP. Experimental Fick diffusivity data were compared with predictions from equilibrium molecular dynamics simulations and excess Gibbs energy calculations using interaction parameters from the literature. Both theoretical methods were not able to predict that the thermodynamic factor is equal to zero at the spinodal composition, stressing the need for new methodologies under such conditions. Thus, new sets of temperature-dependent interaction parameters were developed for the nonrandom two-liquid model, which improve the prediction of the Fick diffusion coefficient considerably. The link between the Fick diffusion coefficient and the nonrandomness of the liquid phases is also discussed.<br

Raman spectroscopy for the determination of hydrogen concentration in liquid organic hydrogen carrier systems - Jander, Julius Hans; Chittem, Pranay Kumar; Kerscher, Manuel; Rausch, Michael Heinrich; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2024)
This work reports on the development of a calibration approach of Raman spectroscopy for the determination of the concentration of dissolved hydrogen (H2) in representative compounds and mixtures of liquid organic hydrogen carrier (LOHC) systems based on diphenylmethane and ortho-benzyltoluene (o-BT). Hydrogen solubility data are measured by the isochoric-saturation method at temperatures and pressures up to 473 K and 7 MPa where Raman spectra of the saturated liquid phase are recorded in parallel. By selecting an appropriate frequency range attributed to the LOHC signatures in isotropic spectra, a calibration which is independent of the LOHC system, the degree of hydrogenation of the LOHC samples, and temperature can be found. The transfer of the calibration to another setup is successfully tested up to 523 K and 6 MPa, where H2 solubilities in the fully hydrogenated o-BT can be determined with an average absolute deviation of 0.009 from theoretically calculated data.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Benzyltoluene; Density; Diphenylmethane; Hydrogen solubility; Isochoric-saturation method; Polarization-difference Raman spectroscopy

Revealing the Effects of Weak Surfactants on the Dynamics of Surface Fluctuations by Surface Light Scattering - Koller, Thomas Manfred; Kerscher, Manuel; Köksal, Anil; Stockerl, Michael; Klein, Tobias; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2023)
Surfactant monolayers at liquid interfaces induce a viscoelastic behavior that influences the dynamics of surface fluctuations probed by surface light scattering (SLS). Recent thermophysical property research on viscosity and interfacial tension of liquid organic hydrogen carrier (LOHC) systems based on diphenylmethane suggested that such viscoelastic effects may also be present here, although not being expected a priori. To prove the hypothesis that the LOHC intermediate cyclohexylphenylmethane (H6-DPM) can induce a surfactant-like behavior, binary mixtures of diphenylmethane (H0-DPM) or dicyclohexylmethane (H12-DPM) with small amounts of H6-DPM were studied by SLS in combination with conventional viscometry and tensiometry and molecular dynamics simulations between (303 and 473) K. Only in mixtures with H0-DPM which has a slightly larger surface tension than H6-DPM, the presence of the latter compound causes a significant effect on the dynamics of surface fluctuations, especially on their damping. In analogy to the concentration-dependent behavior observed for a monolayer of a highly amphiphilic ionic surfactant on the surface of water at ambient temperature, the orientation of H6-DPM molecules with respect to the surface appears to change from a preferentially perpendicular to a parallel alignment with increasing temperature. This demonstrates that viscoelastic effects including accompanied surface orientation effects can be resolved by SLS even for weakly asymmetric surface-active molecules such as H6-DPM in its diluted mixtures with very similar species.
CRIS-Team Scopus Importer:2023-12-22

Thermal Conductivity of Hydrocarbon Liquid Organic Hydrogen Carrier Systems: Measurement and Prediction - Bioucas, Francisco; Piszko, Maximilian; Kerscher, Manuel; Preuster, Patrick; Rausch, Michael Heinrich; Koller, Thomas Manfred; Wasserscheid, Peter; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2020)
In this study, the thermal conductivity of diphenylmethane, benzyltoluene, and dibenzyltoluene and their fully hydrogenated counterparts relevant in the context of the liquid organic hydrogen carrier (LOHC) technology was investigated. For the determination of the thermal conductivity between 298.15 and 323.15 K at atmospheric pressure with an expanded uncertainty of 5% (k = 2), a steady-state guarded parallel-plate instrument was used. To discuss the thermal conductivity over a broader temperature range, measurements were also performed for the density of the pure LOHCs and binary mixtures of diphenylmethane and dicyclohexylmethane between 293.15 and 363.15 K by vibrating tube densimetry as well as for the thermal diffusivity and the Fick diffusion coefficient of binary mixtures of diphenylmethane or dicyclohexylmethane with dissolved hydrogen between 323 and 573 K and pressures between 2.7 and 6.2 MPa by dynamic light scattering (DLS). In general, the measured thermal conductivities of the compounds under investigation decrease with increasing temperature and molar mass and with the degree of hydrogenation. For mixtures of diphenylmethane and dicyclohexylmethane, the concentration dependency of the thermal conductivity shows a distinct nonideal behavior. Based on the measured thermal conductivities of the present pure substances and reference data from the literature for selected cyclic hydrocarbons, a prediction method for the thermal conductivity of such systems could be developed, which requires the molar mass and density as sole input parameters. This correlation represents the thermal conductivity of the selected dehydrogenated and hydrogenated substances and of the studied binary mixture between 298 K and their normal boiling temperature, typically within 5%. By comparison with the thermal conductivity data for diphenylmethane and dicyclohexylmethane deduced from the measurement results for thermal diffusivity and density and from literature data for the specific heat, it was found that the prediction method also allows for a reliable estimation of the thermal conductivity of LOHCs up to a temperature of 573 K, which is the relevant temperature range for hydrogen release from the hydrogenated LOHC compounds.
CRIS-Team Scopus Importer:2020-10-16

Thermophysical properties of diphenylmethane and dicyclohexylmethane as a reference liquid organic hydrogen carrier system from experiments and molecular simulations - Kerscher, Manuel; Klein, Tobias; Schulz, Peter; Veroutis, Emmanouil; Dürr, Stefan; Preuster, Patrick; Koller, Thomas Manfred; Rausch, Michael Heinrich; Economou, Ioannis G.; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2020)
This work contributes to the characterization of the liquid organic hydrogen carrier (LOHC) system diphenylmethane/dicyclohexylmethane by the experimental determination and molecular simulation of the thermophysical properties of the dehydrogenated and fully hydrogenated compounds in a process-relevant temperature range of up to 623 K. Liquid density, liquid viscosity, surface tension and liquid self-diffusion coefficient data measured by vibrating-tube densimeters, surface light scattering, rotational viscometry and NMR spectroscopy are correlated and compared with available literature data which are mostly restricted to temperatures below 473 K. Furthermore, it is demonstrated that an L-OPLS force field (FF) modified in the present study outperforms commonly used FFs from literature in predicting the thermophysical properties of both substances by equilibrium molecular dynamics simulations.<br
Keywords: Density; Equilibrium molecular dynamics simulations; Experiment; Liquid organic hydrogen carriers; Surface tension; Viscosity

Thermophysical properties of the energy carrier methanol under the influence of dissolved hydrogen - Kerscher, Manuel; Jander, Julius Hans; Luther, Fabian; Schühle, Patrick; Richter, Markus; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2023)
Keywords: Isochoric-saturation method; Methanol; Chemical hydrogen storage; Dynamic light scattering; Raman spectroscopy; Thermophysical properties

Thermophysical Properties of the Hydrogen Carrier System Based on Aqueous Solutions of Isopropanol or Acetone - Koller, Thomas Manfred; Jander, Julius Hans; Hewa Kankanamge, Chathura Jayan Kankanamge; Braun, Lena; Chittem, Pranay Kumar; Kerscher, Manuel; Rausch, Michael Heinrich; Klein, Tobias; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Thermophysics, 2024)
One concept for the safe storage and transport of molecular hydrogen (H2) is the use of hydrogen carrier systems which can bind and release hydrogen in repeating cycles. In this context, the liquid system based on isopropanol and its dehydrogenated counterpart acetone is particularly interesting for applications in direct isopropanol fuel cells that are operated with an excess of water. For a comprehensive characterization of diluted aqueous solutions of isopropanol or acetone with technically relevant solute amount fractions between 0.02 and 0.08, their liquid density, liquid viscosity, and interfacial tension were investigated using various light scattering and conventional techniques as well as equilibrium molecular dynamics (EMD) simulations between (283 and 403) K. Polarization-difference Raman spectroscopy (PDRS) was used to monitor the liquid-phase composition during surface light scattering (SLS) experiments on viscosity and interfacial tension. For comparison purposes and to expand the database, capillary viscometry and dynamic light scattering (DLS) from bulk fluids with dispersed particles were also applied to determine the viscosity while the pendant-drop (PD) method allowed access to the interfacial tension. By adding isopropanol or acetone to water, density and, in particular, interfacial tension decrease significantly, while viscosity shows a pronounced increase. The behavior of viscosity and interfacial tension is closely related to the strong hydrogen bonding between the unlike mixture components and the pronounced enrichment of both solutes at the vapor–liquid interface, as revealed by EMD simulations. For an aqueous solution with an isopropanol amount fraction of 0.04, minor variations in interfacial tension and viscosity were found in the presence of pressurized H2 up to 7.5 MPa. Overall, the results from this study contribute to an extended database for diluted aqueous solutions of isopropanol or acetone, especially at temperatures above 323
Keywords: Direct fuel cell; Hydrogen carrier system; Acetone; Aqueous solutions; Isopropanol; Thermophysical properties

Thermophysical properties of the liquid organic hydrogen carrier system based on benzyltoluene considering influences of isomerism and dissolved hydrogen - Kerscher, Manuel; Jander, Julius Hans; Cui, Junwei; Maurer, Lukas A.; Wolf, Patrick; Hofmann, Jonas D.; Köksal, Anil; Zachskorn, Hannah; Auer, Franziska; Schulz, Peter; Wasserscheid, Peter; Rausch, Michael Heinrich; et al. (International Journal of Hydrogen Energy, 2024)
The benzyltoluene (BT)-based liquid organic hydrogen carrier (LOHC) system currently considered for large-scale applications represents a mixture of regioisomers. To characterize this complex system, a comprehensive experimental database for various thermophysical properties of synthesized BT isomers and their mixtures without and with the presence of hydrogen (H2) close to vapor-liquid equilibrium is established using optical and conventional techniques at process-relevant temperatures and pressures up to 573 K and 6 MPa. The surface tension varies by less than 4% among the dehydrogenated (H0-BT) or hydrogenated (H12-BT) isomers. The density and viscosity of mixtures of H0-BT or H12-BT isomers can be described by simple mixing rules with average absolute relative deviations of 0.022% and 0.38%. With increasing H2 pressure, the viscosity remains nearly constant, while the interfacial tension decreases by up to 5%. The thermal and mutual diffusivity of H12-ortho-BT containing dissolved H2 at 6 MPa decrease and increase with increasing temperature.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Benzyltoluene; Hydrogen; Liquid organic hydrogen carrier; Mixture behavior; Regioisomers; Thermophysical properties

Thermophysical properties of the liquid organic hydrogen carrier system based on diphenylmethane with the byproducts fluorene or perhydrofluorene - Kerscher, Manuel; Jander, Julius Hans; Cui, Junwei; Wasserscheid, Peter; Rausch, Michael Heinrich; Koller, Thomas Manfred; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2023)
Keywords: Fluorene; Liquid organic hydrogen carrier; Density; Diphenylmethane; Surface tension; Viscosity

Viscosity and Interfacial Tension of Binary Mixtures Consisting of Linear, Branched, Cyclic, or Oxygenated Hydrocarbons with Dissolved Gases Using Surface Light Scattering and Equilibrium Molecular Dynamics Simulations - Klein, Tobias; Lenahan, Frances; Zhai, Ziwen; Kerscher, Manuel; Jander, Julius Hans; Koller, Thomas Manfred; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Thermophysics, 2022)
In the present study, the influence of the molecular characteristics of the solvent and solute on the dynamic viscosity and interfacial tension of binary mixtures consisting of a liquid with a dissolved gas is investigated using surface light scattering (SLS) and equilibrium molecular dynamics (EMD) simulations. In detail, binary mixtures consisting of linear, branched, cyclic, or oxygenated hydrocarbons and the solutes hydrogen, helium, methane, water, carbon monoxide, or carbon dioxide are studied in the temperature range between (298 and 573) K and for solute mole fractions up to 0.2. With SLS, the liquid dynamic viscosity and interfacial tension of the binary mixtures could be accessed in macroscopic thermodynamic equilibrium with average expanded uncertainties (coverage factor k = 2) of (2.4 and 2.3)%, respectively. While EMD simulations were able to predict the influence of the dissolved gases on the interfacial tension of the binary mixtures, the simulations fail to represent the influence of the dissolved gas on the viscosity. Due to the systematic variation of the solvent and solute molecules, the influence of the molecular characteristics, e.g., in the form of size, shape, or polarity, on the thermophysical properties of the mixtures is discussed. Dissolving carbon dioxide, e.g., leads to a reduction of both properties by up to 60% compared to the properties of the pure solvent. Dissolved helium, on the other hand, has only a small influence on the properties of the pure solvent. The influence of dissolved water was found to be negligible in mixtures with an alkane but strongly increases both properties when dissolved in an alcohol, which may be explained by the formation of hydrogen bonds.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Binary mixtures; Gases; Hydrocarbons; Interfacial tension; Molecular dynamics simulations; Surface light scattering; Viscosity

Viscosity and Interfacial Tension of Binary Mixtures of n-Hexadecane with Dissolved Gases Using Surface Light Scattering and Equilibrium Molecular Dynamics Simulations - Klein, Tobias; Lenahan, Frances; Kerscher, Manuel; Jander, Julius Hans; Rausch, Michael Heinrich; Koller, Thomas Manfred; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2021)
In the present study, the influence of dissolved gases on the viscosity and interfacial tension of n-hexadecane is investigated using surface light scattering (SLS) experiments and equilibrium molecular dynamics (EMD) simulations. In detail, binary mixtures of n-hexadecane with the solutes hydrogen, helium, methane, water, nitrogen, carbon monoxide, and carbon dioxide are studied in the temperature range between (298 and 573) K and for two solute mole fractions up to 0.2. With SLS, the liquid viscosity and interfacial tension of the binary mixtures were accessed with average expanded uncertainties (coverage factor k = 2) of 2.3 and 1.9%, respectively. By comparing the thermophysical properties of the binary mixtures with the ones of pure n-hexadecane, the influence of the dissolved gases is discussed. For the two lightest gases hydrogen and helium as well as for the solute water, only a small influence of the dissolved gas could be found. For the other gases, a decrease of up to 30% is found for both the viscosity and interfacial tension. While the results for the interfacial tension of the binary mixtures from EMD simulations agree well with the results from SLS measurements, the simulations fail to predict the influence of the dissolved gas on the viscosity accurately. Finally, the enrichment of the solute molecules at the vapor-liquid interface analyzed using EMD simulations is linked to the interfacial tension results.
CRIS-Team Scopus Importer:2021-08-06

Viscosity and Surface Tension of Benzene at Saturation Conditions from Surface Light Scattering - Kerscher, Manuel; Fröba, Andreas Paul; Koller, Thomas Manfred (International Journal of Thermophysics, 2021)
In the present study, the liquid viscosity and surface tension of benzene was determined at saturation conditions from surface light scattering (SLS) experiments between (283 and 393) K. Based on the application of the hydrodynamic theory for surface fluctuations at the vapor-liquid phase boundary which was successfully validated by the measurements, a simultaneous determination of liquid viscosity and surface tension with average relative expanded uncertainties (k = 2) of (1.0 and 0.8)% was achieved. Agreement between the measurement data and reference values available in the literature was found for the viscosity and in general also for the surface tension, where benzene constitutes a recommended reference material of relatively moderate surface tension values. All these findings demonstrate for a repeated time that SLS is a suitable method for the investigation of fluids including reference fluids such as benzene, which enables a sound representation of its surface tension, presumably as a result of a rather random molecular orientation at the surface. Overall, the experimental results from this work could contribute to an improved data situation for benzene, in particular with respect to providing viscosities and surface tensions at true saturation conditions.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Benzene; Surface light scattering; Surface tension; Viscosity

Viscosity and Surface Tension of Fluorene and Perhydrofluorene Close to 0.1 MPa up to 573 K - Cui, Junwei; Kerscher, Manuel; Jander, Julius Hans; Rüde, Timo; Schulz, Peter; Wasserscheid, Peter; Rausch, Michael Heinrich; Koller, Thomas Manfred; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2022)
In the present study, the liquid viscosity and surface tension of fluorene (H0-F) and its fully hydrogenated counterpart perhydrofluorene (H12-F), representing process-relevant byproducts of the liquid organic hydrogen carrier (LOHC) system based on diphenylmethane and dicyclohexylmethane and potentially interesting LOHC compounds by themselves, were determined close to 0.1 MPa using different experimental methods. Besides surface light scattering (SLS) allowing for a simultaneous access to both properties up to 573 K, conventional methods in the form of capillary viscometry and pendant-drop tensiometry were applied up to (473 and 523) K, respectively. Furthermore, the liquid density of H12-F was measured by vibrating-tube densimetry from (283 to 473) K. While agreement of the viscosity and surface tension results obtained by SLS and the conventional methods is found in the case of H12-F, this is not given for H0-F, especially with respect to its surface tension, which seems to be caused by SLS-specific effects. H0-F exhibiting a melting point of about 384 K shows larger values for density, surface tension, and viscosity compared to H12-F being liquid at 283 K. The latter compound features stereoisomerism which appears to have a pronounced effect on the thermophysical properties. This could be deduced by comparison with the very limited amount of experimental data for the fluorene-based substances that are available in the literature so far. The extension of the thermophysical property database for H0-F and H12-F under process-relevant conditions can be useful for future studies, particularly in the field of chemical hydrogen storage.
CRIS-Team WoS Importer:2022-09-30

Viscosity, Interfacial Tension, and Density of 2-Propanol and Acetone up to 423 K by Surface Light Scattering and Conventional Methods - Kerscher, Manuel; Braun, Lena; Jander, Julius Hans; Rausch, Michael Heinrich; Koller, Thomas Manfred; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Thermophysics, 2024)
Despite the extensive use of 2-propanol and acetone in a wide range of applications in the chemical industry and in energy engineering, there is a lack of experimental data in the literature for their thermophysical properties including viscosity, interfacial tension, and density, especially at elevated temperatures beyond the respective normal boiling points. In the present study, the liquid viscosity and interfacial tension were determined simultaneously by surface light scattering (SLS) with average expanded uncertainties of (1.7 and 0.9)% at or close to saturation conditions for temperatures between (273 and 403) K. Furthermore, capillary viscometry (CV) and vibrating-tube densimetry were employed to measure the liquid viscosity at ambient pressure of 0.1 MPa from (283 to 353) K and the liquid density close to saturation conditions between (278 and 423) K. The obtained density data were used for the evaluation of both SLS and CV experiments. In comparison with literature data, the present density data show agreement for 2-propanol over the entire temperature range. In contrast, deviations of up to 0.5% at the maximum temperature can be found for acetone. For the viscosity and interfacial tension at low temperatures, agreement of the measurement results among each other and with literature data is mostly found. At elevated temperatures, the increasing deviations of the present experimental viscosity and interfacial tension data from recommended correlations indicate a lack of reliable data needed for their development. Overall, this work contributes to an improvement of the database for viscosity, interfacial tension, and density of 2-propanol and acetone over a wide temperature range up to 423 K.
CRIS-Team Scopus Importer:2023-12-29
Keywords: 2-Propanol; Acetone; Density; Interfacial tension; Surface light scattering; Thermophysical properties; Viscosity

Viscosity, surface tension, and density of binary mixtures of the liquid organic hydrogen carrier diphenylmethane with benzophenone - Kerscher, Manuel; Jander, Julius Hans; Cui, Junwei; Martin, Max; Wolf, Moritz; Preuster, Patrick; Rausch, Michael Heinrich; Wasserscheid, Peter; Koller, Thomas Manfred; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
The liquid organic hydrogen carrier (LOHC) diphenylmethane may react to benzophenone in the presence of air, especially at elevated temperatures. Therefore, information about the influence of benzophenone added to diphenylmethane on process-relevant thermophysical properties is required. In the present contribution, the liquid viscosity, surface tension, and liquid density of binary mixtures of diphenylmethane with benzophenone are determined between (283 and 573) K using complementary experimental methods. Investigations on the surface tension by the pendant-drop method and surface light scattering indicate molecular orientation effects of benzophenone at the vapor-liquid interface. With increasing benzophenone content, an increase in density, surface tension, and especially viscosity is found. For the latter property, a distinct change in the temperature dependence is observed at the transition from the liquid to the supercooled liquid state. Furthermore, water dissolved in benzophenone causes changes within 15% and 3% relative to the viscosity and surface tension of benzophenone, respectively.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Benzophenone; Density; Diphenylmethane; Liquid organic hydrogen carrier; Surface tension; Viscosity

Viscosity, surface tension, and density of the liquid organic hydrogen carrier system based on diphenylmethane, biphenyl, and benzophenone - Jander, Julius Hans; Kerscher, Manuel; Cui, Junwei; Wicklein, Johannes; Rüde, Timo; Preuster, Patrick; Rausch, Michael Heinrich; Wasserscheid, Peter; Koller, Thomas Manfred; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
Keywords: Biphenyl; Liquid organic hydrogen carrier; Surface tension; Diphenylmethane; Eutectic mixture; Viscosity